Carboxypeptidase rescue after high-dose methotrexate. Issue 2 (12th March 2012) - Benitez, B.; Capilla, E.; Gonzalez, L.; de Miguel, M.P. Garcia; Rueda, C.; Casado, G.; Varela, H.; Roldan, T.; Bravo, M.; Herrero, A.
Abstract : Background: High-dose methotrexate may cause acute nephrotoxicity because it is mostly excreted by the renal route. Carboxypeptidase G2 is an enzyme that hydrolyses methotrexate rapidly to the inactive metabolites DAMPA and glutamate. The criteria that justify the use of carboxypeptidase in the hospital studied are: methotrexate plasma concentration >10 µM/L, 48 h after administration or increase of creatinine by 100%, 24 h after infusion. Purpose: The aim of this study was to check that carboxypeptidase was being used correctly according to the hospital's criteria and to evaluate patient response to treatment. Materials and methods: Retrospective study of patients who received carboxypeptidase in the last five years. The data collected were: diagnosis, age, doses of methotrexate and carboxypeptidase, methotrexate and creatinine plasma levels. Results: Eighty patients were treated with high dose methotrexate (5 g/m 2 ) and 8 of them (10%), diagnosed with acute lymphoblastic leukaemia, needed a rescue with 50 IU/kg of carboxypeptidase 48 h after infusion. The mean age was 8.87 years (3-13). The mean time to recovery renal function was 7.28 days (4-17) after administration of carboxypeptidase. Conclusions: All patients fulfilled at least one of the two criteria that justified carboxypeptidase administration. This drug offers an alternative rapid route for methotrexate elimination. The role of the pharmacist is important to ensure proper use of carboxypeptidase due to the high cost of the drug.